Funcionarios. (UNED, 2024)
De izquierda a derecha aparecen Delio Mora Campos, Yirlania Quesada Boniche, Pablo Ramírez Mendoza (Jefe), Alvaro Alcazar Hernández, sentados aparecen Ana Cristina Carvajal Solano, Ingrid Romero Mora y Flor Iveth Rivera Mora